PENGARUH PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI BANGUN DATAR KELAS III SD NEGERI 1 TRENCENG SUMBERGEMPOL TULUNGAGUNG - Sururi Mahmudah; Yasip (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low student achievement in mathematics, especially in the topic of plane figures, is often caused by the use of less engaging teaching methods. Teachers tend to rely on lectures, making students less active and more likely to struggle with understanding the material. This study aims to examine the effect of the Teams Games Tournament (TGT) learning model on the learning outcomes of third-grade students.This research used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The sample consisted of 18 students from class III-B at SD Negeri 1 Trenceng as the experimental group and 12 students from class III-A at SD Negeri 2 Trenceng as the control group. Data were collected using pre-tests and post-tests that had been tested for validity and reliability. The data were analyzed using Jamovi software. The results showed that the Teams Games Tournament (TGT) model had a significant effect on students’ learning outcomes. The average pre-test score in the experimental group increased from 62.2 to 88.9, while the control group improved from 60.0 to 74.2. The t-test produced a significance value of p < 0.001. The data also met the assumptions of normality and homogeneity.In conclusion, the Teams Games Tournament (TGT) model is effective in improving the learning outcomes of third-grade students in the topic of plane figures at the elementary school level.